العاميّة وتأثيرها في تعليم العربيّة الفصحى - بن السايح د.عائشة (Université de M'sila, 2020)
ملخص: إن استعمال اللهجة إلى جانب اللغة الفصحى حقيقة لا يمكن إنكارها، فهي كذلك في كل اللغات، إلاّ أنّ المشكلة هي حضورها في التعليم، وقد سعت هذه الدراسة إلى إبراز أثر العامية في تعليم اللغة العربية الفصحى في المرحلة الابتدائية في الجزائر، وخلصت الدراسة إلى جملة من التوصيات الداعية إلى الاهتمام باللغة العربية، و الاسهام في حل مشكلاتها في مجال التعليم. Abstract: The use of dialect in addition to the language of pharaism is an undeniable fact, as it is in all languages, but the problem is its presence in education, which sought to highlight the impact of colloquial language on the teaching of the Arabic language at the primary level. The study concluded a number of recommendations calling for attention to Arabic and for contributing to solving its problems in the field of education.
Keywords: الكلمات المفتاحية: عربية فصحى- عامية - تأثير – تعليم – مرحلة ابتدائية..Keywords: Arabic healthy, dialect , effect, Education - primary.